Permasalahan Pengadaan Hak Atas Tanah untuk Jalan Tol Padang-Sicincin di Nagari Kapalo Hilalang Kecamatan 2X11 Kayu Tanam Kabupaten Padang Pariaman - Musfita, Chifa Dwi; Rahmat, Indra; Asril, Asril (Asian Journal of Science, Technology, Engineering, and Art, 2023)
This study aims to find out the problems in the procurement of land rights and to describe the efforts made by the government to the community in dealing with the procurement of land rights in Nagari Kapalo Hilalang, 2X11 Kayu Tanam District, Padang Pariaman Regency. The method used in this study is descriptive qualitative, data collection with techniques purposive sampling. The research location was Nagari Kapalo Hilalang, District 2X11 Kayu Tanam, Padang Pariaman Regency. The informants in this study were the Padang Pariaman Regency National Land Agency, elements of the regional government of Nagari Kapalo Hilalang District 2X11 Kayu Tanam, elements of traditional stakeholders and the nagari community who were affected by the construction of the toll road. Data collection techniques are through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation and conclusion. The results of the study showed that the problems in procuring land rights were that the land owner was not in place or where the owner was, the socialization that was carried out did not involve all affected residents, there was a lawsuit filed by a datuak and a lack of awareness to make a basis for rights or proof of land ownership. From the results of the research above, it can be concluded that the problem of procuring land rights in Nagari Kapalo Hilalang can be resolved by providing more intense outreach to the affected communities, resolving disputes between people after resolving the dispute and then making a basis for rights or proof of land ownership, then the party authorized to resolve the matter to the district court by bringing the basis of rights or proof of ownership of the land so that the court can provide the compensation money that has been entrusted by the toll operator to the party concerned.